Field evaluation of talc formulation of Trichoderma for the management of Fusarium wilt in watermelon - N.P. SINGH, R. RAMESH* and (Indian Phytopathology, 2017)
Wilt of watermelon caused by Fusarium oxysporum. f.sp. niveum is one of the major constraint in watermelon production in coastal regions. In this study, twenty seven isolates of Trichoderma were evaluated for their ability to inhibit the pathogen growth. Talc formulations of four selected Trichoderma isolates were evaluated in the field. Incidence of wilt in the biocontrol treatments was less than 10 per cent in trial 1 and less than seven percent in trial 2 and less than four per cent in trial 3 during 2012-13 while control plot recorded 21 to 34 per cent incidence. During 2013-14, incidence of wilt was less than seven per cent in trial 1 and less than 15 percent in trial 2 in the biocontrol treatments while control plot recorded 19 and 28 per cent incidence. From the pooled data of all the five trials it was observed that 70 to 80 per cent reduction of wilt and 27 to 30 per cent increase in number of fruits in biocontrol treated plots over untreated control. From the study, it is concluded that seedling drench with talc formulation of Trichoderma reduced Fusarium wilt and increased yield in watermelon.